Work, Inc. A Philosophical Enquiry - Laycock, Henry (Labour / Le Travail, 1991)
The article reviews the book, "Work, Inc. A Philosophical Enquiry," by Edmund F. Byrne.
Keywords: BOOKS – Reviews; FINE; Sidney; Nonfiction; VIOLENCE in the Model City: The Cavanaugh Administration; Race Relations & the Detroit Riot of 1967 (Book); violence